2012
DOI: 10.1371/journal.pone.0051446
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Mass Index on Breast Cancer during Premenopausal and Postmenopausal Periods: A Meta-Analysis

Abstract: ObjectiveThere is no universal consensus on the relationship between body mass index (BMI) and breast cancer. This meta-analysis was conducted to estimate the overall effect of overweight and obesity on breast cancer risk during pre- and post-menopausal period.Data SourcesAll major electronic databases were searched until April 2012 including Web of Knowledge, Medline, Scopus, and ScienceDirect. Furthermore, the reference lists and related scientific conference databases were searched.Review MethodsAll prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
149
6
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(170 citation statements)
references
References 57 publications
11
149
6
4
Order By: Relevance
“…Results of previous meta-analysis studies suggested that high BMI during premenopausal period may protect against breast cancer development in later life, although the association did not reach statistical significance (Cheraghi et al 2012). This trend has been also reported in several other studies showing a significant inverse association between body weight and breast cancer incidence in premenopausal women (Harris et al 2011a, b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of previous meta-analysis studies suggested that high BMI during premenopausal period may protect against breast cancer development in later life, although the association did not reach statistical significance (Cheraghi et al 2012). This trend has been also reported in several other studies showing a significant inverse association between body weight and breast cancer incidence in premenopausal women (Harris et al 2011a, b).…”
Section: Discussionmentioning
confidence: 99%
“…This trend has been also reported in several other studies showing a significant inverse association between body weight and breast cancer incidence in premenopausal women (Harris et al 2011a, b). In contrast, the same meta-analysis demonstrated that increased BMI during postmenopausal period could significantly increase the risk of breast cancer development (Cheraghi et al 2012). The increased risk in postmenopausal women associated with being overweight and/or obese is due to the fact that adipose tissue is the major source of estrogen following menopause (Cauley et al 1989;Key et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, obesity during pre-teen years (ages 5-10) is inversely related to breast cancer risk (Baer et al, 2010). On the other hand, obesity after menopause is positively related to breast cancer incidence (Bates and Carmichael, 2004;Lahmann et al, 2004;Cheraghi et al, 2012;Phipps et al, 2012;Xu et al, 2012). Although this is fairly well established, the relationship between premenopausal obesity and breast cancer risk remains less clear.…”
Section: Obesitymentioning
confidence: 99%
“…Tercero, las cohortes que han evaluado la relación entre cáncer y obesidad se han centrado en personas de edad media, lo que probablemente no refleja los riesgos a edades jóvenes o envejecidas 16 . Cuarto, los estimados de FAP% para cáncer de mama debieran ser calculados diferencialmente en mujeres premenopáusicas y postmenopáusicas, dado que la evidencia epidemiológica señala que la obesidad estaría asociada a un mayor riesgo de este cáncer sólo en postmenopáusicas 17 . Finalmente, los datos actuales de incidencia representan el impacto por exposición a obesidad en décadas pasadas, donde las prevalencias eran más bajas que las actuales 18 .…”
Section: Discussionunclassified